Raised iron levels in wet- ground vigna unguiculata and capsicum frutescens using domestic grinding techniques (2014)
The biosafety of commonly used domestic grinding techniques was investigated; the effects of attrition mills using new (attrition mill 1) and old (attrition mill 2) plates, wooden mortar and pestle, grinding stone and electric blender on iron content of wet-ground staple foods, Vigna unguiculata (cowpea) and Capsicum frutescens (pepper) were examined in this study. Attrition mill 1 was in use 4 weeks prior to this study while the attrition mill 2 had newly installed grinding plate. The wet-ground pepper and cowpea were analyzed using Atomic Absorption Spectrophotometer (AAS). The iron contents of wet- ground foods (pepper and cowpea) from both attrition mills were significantly higher (p>0.05) than iron content of ground food using other methods of grinding. A 30-40 folds increases in the iron content of ground food samples were detected using attrition mills. Ground pepper from attrition mill 1 showed higher iron contents (4300±474.35mg) than pepper ground in attrition mill 2 (3199±281.68mg). These values are higher than recommended dietary allowances for iron intake. The increased iron content in ground pepper and cowpea observed in the present study confirmed the high risk of iron overloading using attrition milling. The level of contamination of ground food increased with use in attrition mills as a result of wear and tear of grinding plates.